The Influence of Managerial Ability and Earnings Quality on Financial Reporting Fraud in Energy Sector Companies Listed on the Indonesia Stock Exchange 2020–2024 - Susi Rahmawati; Intan Pramesti Dewi (LP2M IAIN Palopo, 2026)
The purpose of this study is to analyze the effect of managerial ability and earnings quality on financial statement fraud in energy sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. The research hypothesis states that managerial ability and earnings quality contribute to financial statement fraud. A quantitative approach was implemented using secondary data sourced from the annual reports of energy sector companies. The research population included 89 companies, with probability sampling techniques using the proportionate stratified random sampling method, resulting in 73 companies as research samples with a total of 360 observations. Managerial ability was measured using the firm efficiency approach, income quality was measured using the quality of income ratio, while financial statement fraud was measured using the Beneish M-Score model. The data analysis techniques used included descriptive statistical analysis and panel regression with the Common Effect Model. The results found that managerial ability and income quality had a significant positive effect on financial statement fraud, both simultaneously and partially. These findings indicate that managerial ability and apparent income quality can be exploited opportunistically by management under certain conditions of pressure. These findings suggest that high managerial ability and seemingly high-quality earnings may be used opportunistically by management under certain pressures. The study highlights the importance of strengthening corporate governance mechanisms and financial reporting oversight, particularly in the energy sector, which is characterized by high fraud risk. The findings also provide implications for future research to incorporate additional variables and alternative fraud detection approaches.